A non-dominated sorting genetic algorithm III using competition crossover and opposition-based learning for the optimal dispatch of the combined cooling, heating, and power system with photovoltaic thermal collector - Zou, Dexuan; Li, Mengdi; Ouyang, Haibin (Engineering applications of artificial intelligence, 2024)
A photovoltaic thermal collector (PV/T) is incorporated into the combined cooling, heating, and power (CCHP) system to decrease primary energy consumption, operation cost and carbon dioxide emission. Six CCHP scenarios based on three strategies are investigated for the energy utilization of the CCHP system. Also, a non-dominated sorting genetic algorithm III using competition crossover and opposition-based learning (NSGA-III-CO) is proposed for the six scenarios. The competition crossover determines the starting point of search in the decision space, and more potential regions can be exploited sufficiently. The opposition-based learning (OBL) carries out random searches and facilitates the convergence of the population. In addition, a constraint handling approach (CHA) is presented to decrease the constraint violations of the infeasible individuals and turn them into feasible individuals, and it guarantees the feasibility of the population. Experimental results suggest that each CCHP scenario with PV/T is more efficient than the one with photovoltaic panel (PV) and the one neglecting PV/T and PV, and it achieves the lowest primary energy consumption, operation cost and carbon dioxide emission. Also, NSGA-III-CO and the other three algorithms are applied to the six CCHP scenarios with PV/T, and it obtains the highest hypervolume and coverage rate for each scenario. [Display omitted] •This paper studies dispatch of combined cooling, heating, and power system (CCHP).•The CCHP involves photovoltaic thermal collector.•An improved NSGA-III is proposed for CCHP.•The improved NSGA-III has exhibited good comprehensive performance for CCHP.•A constraint handling approach is presented to satisfy the constraints of CCHP.